2009
DOI: 10.5937/geopan0901011s
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of the principle of sustainable development in the Special Nature Reserve 'Stari Begej-Carska bara' (Vojvodina, Serbia)

Abstract: Special nature reserve "Stari Begej-Carska bara" is one of the last remaining wetlands in Vojvodina. Essential natural assets-hydrographic characteristics, have undergone significant changes, because of which the Reserve is still endangered even today. To overcome these obstacles in the management of the Reserve, we have to turn to the idea of sustainable development, which should in addition to the ecological criteria comprise socio-cultural and economic criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The area of SNR "Carska Bara" is well studied, both from the aspect of natural basis and from the aspect of tourism, while the population of the Reserve and the immediate environment was the subject of only a few works and monographs, usually by the same authors. All these studies (Stojanović, 2005;Stojanović, et al, 2011;Stojanović, Pavić, & Ristanović, 2009) have indicated a decreasing trend in population numbers in all the settlements. The results of the analysis of the local population characteristics conducted here coincide with their conclusions.…”
Section: Discussionmentioning
confidence: 98%
“…The area of SNR "Carska Bara" is well studied, both from the aspect of natural basis and from the aspect of tourism, while the population of the Reserve and the immediate environment was the subject of only a few works and monographs, usually by the same authors. All these studies (Stojanović, 2005;Stojanović, et al, 2011;Stojanović, Pavić, & Ristanović, 2009) have indicated a decreasing trend in population numbers in all the settlements. The results of the analysis of the local population characteristics conducted here coincide with their conclusions.…”
Section: Discussionmentioning
confidence: 98%